SIZE OF APICAL CONSTRICTION IN DIFFERENT TYPES OF PERMANENT TEETH - Evgeni Stanev; Sevda Yantcheva (Journal of IMAB)
Background: The final size of the apical root canal preparation has been a contraversion issue for a long time. The enlargement of the apical portion of the root canal may severely affect endodontic prognosis. Preparation of the apical zone to a larger file size may negatively affect the ability to control the filling material during root canal obturation. An excessively expanded apical zone increases the risk of overfilling, which has been shown to be associated with a reduced success rate. This article aims to review research papers on the anatomical natural diameter of the apical root canal constriction, which is the endpoint of the endodontic preparation and should determine the appropriate size of the apical and root canal preparation. Review Results: In the review, we have included various scientific articles from recent years that comment on the size and shape of the apical constriction in different groups of teeth. We have summarized the results in graphs that give a visual idea of ​​the differences in the sizes of the different apical constrictions. Conclusion: The root apex is morphologically a challenging zone. The endodontist should have detailed knowledge of anatomic variation and mechanics challenges involved in treating apical third to manage endodontic therapy effectively. More research is needed to elucidate the influence of the size of the apical constriction on the apical stop preparation.